DAKWAH USTADZ DALAM MEMBINA AKHLAK REMAJA MUSHALLA AL-LATIF TANJUNG GADING BANDAR LAMPUNG - , (Jurnal el-Huda, 2022)
Adolescence is an important period in the span of human life. This period is known as a transitional period, a period in which there are rapid changes, a problematic age, a period of individuals seeking self-identity, a frightening age, an unrealistic period, and a period of adulthood. Therefore, teenagers are very dependent on who they hang out with, exchange ideas and learn. Because teenagers really need someone who is able to give enthusiasm in learning in order to achieve good achievements in school, invites in goodness, and of course that figure can provide a personal example in doing virtues in their daily lives. In conducting this research, the author uses a qualitative approach with a descriptive method of character study. And doing this research the author wants to find answers about how the process of Da'wah Activities implemented by Ustadz Syarifudin in fostering the morals of teenagers at the Al-Latif Mushalla Tanjung Gading Peace in Bandar Lampung. Through observation, interviews, and documentation. From this research, it can be concluded that Ustad Syarifudin's da'wah activity is by lecturing with various Habluminnas material, while the method of delivery is by Bil-hikmah, Mauizhah Hasanah, and Mujlah Bil Lati Hiya Ahsan. After the material was delivered by the Ustadz, teenagers were given the opportunity to ask questions so that the teenagers understood the material and tried to change their behavior.